2001
DOI: 10.1080/713655016
|View full text |Cite
|
Sign up to set email alerts
|

Stability of dietary ascorbic acid and the effect of supplementation on reproductive performance of broiler breeder chickens

Abstract: 1. The purpose of the study was to determine the stability of dietary ascorbic acid and the reproductive responses of broiler breeder chickens to supplemental 75 mg ascorbic acid/kg diet. 2. Six breeder flocks of 13,000 birds each were studied. Egg production, eggshell porosity, fertility, hatchability and plasma ascorbic acid were measured. 3. Storage of the diets under dry heat resulted in a linear decrease in ascorbic acid content and the rate of decline was 5-fold higher in the supplemented diet. 4. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 32 publications
0
10
0
Order By: Relevance
“…Since ascorbic acid is synthesised in the chicken body and not found in the egg its direct role in internal egg quality is questionable. The results of Creel et al. (2001) did not provide evidence of a beneficial reproductive response to the inclusion of ascorbic acid in commercial broiler breeder diets.…”
Section: Antioxidant Defences Of the Developing Embryomentioning
confidence: 72%
“…Since ascorbic acid is synthesised in the chicken body and not found in the egg its direct role in internal egg quality is questionable. The results of Creel et al. (2001) did not provide evidence of a beneficial reproductive response to the inclusion of ascorbic acid in commercial broiler breeder diets.…”
Section: Antioxidant Defences Of the Developing Embryomentioning
confidence: 72%
“…Dietary supplementation with AA improved the production performance and immunity status of old laying hens (72 weeks old) subjected to severe heat stress conditions [ 10 ]. However, some results have shown that the supplementation of AA was found to have no effect on the production performance of laying hens (31 weeks old) under oxidant stress [ 11 ] and broiler breeder chickens [ 12 ]. Such inconsistent results regarding AA supplementation prompted an examination of the changes in distribution and transportation of AA in different tissues and GLO enzyme activity in poultry of different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue samples were homogenized in 5% cold trichloroacetic acid for about 10 s using a Polytron (Model MR 2100, Kinematica AG, Switzerland) homogenizer set at 22. The homogenate was centrifuged at 16 000 g for 1 min and the supernatant used to measure ascorbic acid ( Creel et al, 2001). Tissue samples were processed and assayed within 3 weeks storage at −20 °C.…”
Section: Biochemical Measurementsmentioning
confidence: 99%
“…The responses of poultry to supplemental AsA have been inconsistent ( Scott , 1975; Pardue and Thaxton , 1986; Keshavarz , 1996; Okoye et al, 1998; Chen and Balnave , 2001; Creel et al, 2001). The equivocal responses may be ascribed to dietary and/or environmental factors that influence ascorbate metabolism and were confounded in the experiments.…”
Section: Introductionmentioning
confidence: 99%